COVID-19 and CAR T cells: a report on current challenges and future directions from the EPICOVIDEHA survey by EHA-IDWP - Busca, Alessandro; Salmanton-García, Jon; Corradini, Paolo; Marchesi, Francesco; Cabirta, Alba; Di Blasi, Roberta; Dulery, Remy; Lamure, Sylvain; Farina, Francesca; Weinbergerová, Barbora; Batinić, Josip; Nordlander, Anna; et al. (Blood advances, 2022)
The EHA-IDWP developed an observational registry collecting data on COVID-19 infection in patients who received CAR T-cell therapy. Prevalence of COVID-19 was 4.8%, and overall mortality was 50%, highlighting the need for prevention of infection in these patients.
Keywords: Immunotherapy, Adoptive; COVID-19; T-lymfocyty; chimerické antigenní receptory; Receptors, Chimeric Antigen; Humans; imunoterapie adoptivní; lidé; T-Lymphocytes